Exploring Learner Perceptions and Motivation of AI-Assisted Writing Tools in English for Specific Purposes Classrooms - Dwita Laksmita Rachmawati; Yufenti Oktafiah; Sri Hastari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The integration of Artificial Intelligence (AI) in education has opened new possibilities for enhancing teaching and learning, particularly in English for Specific Purposes (ESP) classrooms. This study examines the perceptions and motivations of third-semester management students at Universitas Merdeka Pasuruan regarding AI-assisted writing tools in their ESP courses. Using a qualitative case study design, data were collected through semi-structured interviews with 20 participants. Thematic analysis identified three key themes: perceptions of AI tools' usefulness, motivational factors, and challenges. Participants viewed AI tools as beneficial for improving writing skills, providing personalized feedback, and supporting collaborative learning. Motivational drivers included simplifying complex tasks and promoting independent learning. However, challenges such as technical difficulties and limited proficiency in using AI features were highlighted. The findings emphasize the potential of AI in enhancing ESP instruction, provided challenges are addressed with adequate training and support. Despite its small sample size and focus on a single institution, the study offers insights into the pedagogical implications of AI integration in specialized language education. It also provides practical recommendations for optimizing AI use in ESP classrooms while calling for broader research in diverse educational contexts.